Korespondensi Bahasa Kui, Hamap, dan Kamang di Kabupaten Alor - Sanubarianto, Salimulloh Tegar; Weking, Christina Terentje (Humanitatis : Journal of Language and Literature, 2020)
Abstract Alor is a unique phenomenon in comparative historical linguistics. The heterogeneity of the languages there has long been interesting to study. One of them is this research. This study aims to measure the geographical correspondence of Kui, Hamap, and Kamang which are so close geographically. Data were collected by interview method and then analyzed by lexicostatistics. As a result, Kui has a level of correspondence 18,5% with Hamap. Kui has a 14 % level of correspondence with Kamang. Then, the Hamap language has a 12% level of correspondence with Kamang. All three have a high level of language difference even though the speakers lif side by side. Keywords: Kui, Hamap, Kamang, correspondence language